Índice de Integridade Biótica para o município de Sorocaba (SP) utilizando comunidades de peixes - Silva, Guilherme (2018)
The Biotic Integrity Index has been an effective biomonitoring tool utilizing freshwater fish assemblages. In tropical and subtropical countries, however, its use over time has been developing, although adaptation in these regions has begun more recently. This study aimed at the creation of a Biotic Integrity Index for the municipality of Sorocaba - SP, where it aims to assist in the monitoring of aquatic environments in the urban zone using as bioindicators the fish of streams. A total of 2492 individuals were collected in a total of 27 stretches, 23 in the urban area of the city of Sorocaba and 4 in the Ipanema National Forest in Iperó. An environmental protocol was also applied in all the excerpts to verify the physical characteristics of the streams and later used to promote correlations between the biotic variables. Seven variables were selected to compose the Biotic Integrity Index, being separated into three groups with a response capacity, such as species diversity, habitat and trophic function. Two streams were classified as excellent (7.5%), five as good (18.5%), five regular (18.5%), eight poor (29.5%), two very poor (7.5%), and five without fish (18.5%). The biotic integrity index proposed for this work presented a satisfactory correlation between the environmental conditions and the fish communities due to the presence of a environmental gradient capable of generalizing impacts in the urban region of the city of Sorocaba. This work has demonstrated that studies like this one besides being able to promote applicability and development of methods for environmental biological evaluations, also has as consequence a better knowledge of the freshwater fishes.